A Teoria de segmentação face à satisfação do consumidor de serviços bancários: um estudo de caso em um banco de varejo - Chaves, Marcos Oswaldo Barcellos (2001)
There is a intensity change within financial services industry: deregulation, technology, joint ventures and, in Brazil, privatization, increase of foreign competitors and fall of industry participating from 31 per cent to 5,4 per cent in Brazilian GDP.In this context financial institutions are working very hard to improve their market share, besides promoting customer retention and creating customer loyalty.In this paper we are presenting the scenario of industry in the 90's, opportunity to use segmentation and relationship strategies used by banks through distribution channels.The purpose of this study is to examine the relationship between customer satisfaction and segmentation. To ascertain whether such a link exists, a primary study of 3.378 individuals was conducted in two branches at Rio de Janeiro in March 2001. The results suggest that there is little relationship between customer satisfaction and segmentation, besides other qualitative findings.